Psychometric validation of the WHO-5 and WHO-4 well-being index scales for assessing psychological well-being and detecting depression in Japanese school-aged children: a community-based study - Adachi, Masaki; Takahashi, Michio; Mori, Hiroyuki; Nishimura, Tomoko; Osada, Makoto; Adachi, Minami; Monden, Rei; Wakuta, Manabu; Nakamura, Kazuhiko (Frontiers in Public Health, 2025)
IntroductionThe 5-item World Health Organization Well-Being Index (WHO-5) is widely used to assess psychological well-being, but its psychometric properties in younger populations, particularly in non-Western settings, remain underexplored. This study aimed to assess the validity and reliability of the Japanese version of the WHO-5 (WHO-5-J) and a culturally adapted four-item version (WHO-4-J), which excludes a culturally sensitive item (“I have felt cheerful and in good spirits”) and uses a simplified four-point Likert scale to minimize cognitive burden among Japanese school-aged children.MethodsData were collected from a large community-based sample of 6,983 students aged 10–15 years (Grades 4–9) in Hirosaki City, Japan. We evaluated the factorial validity and internal consistency of the WHO-5-J and WHO-4-J using exploratory and confirmatory factor analyses. Measurement invariance across age and gender groups was examined with multi-group confirmatory factor analyses. Receiver operating characteristic analyses were conducted to determine optimal cutoff scores for detecting psychological distress.ResultsExploratory and confirmatory factor analyses supported the factorial validity and internal consistency of both the WHO-5-J (α = 0.84–0.88; ω = 0.86–0.91) and WHO-4-J (α = 0.82–0.88), confirming their unidimensional structures. Multi-group confirmatory factor analyses demonstrated full scalar measurement invariance across age and gender groups. Receiver operating characteristic analyses identified optimal cutoff scores with area under the curve values ranging from 0.80 to 0.85, indicating good diagnostic accuracy for psychological distress.DiscussionOverall, the WHO-4-J demonstrated psychometric properties comparable to those of the WHO-5-J, supporting its practical utility as a culturally appropriate tool for assessing psychological well-being and screening for depression in Japanese youth. These findings underscore the importance of cultural adaptation and developmentally appropriate scaling for accurately assessing psychological well-being in diverse, non-Western child populations.